2017
DOI: 10.2989/16085906.2017.1343740
|View full text |Cite|
|
Sign up to set email alerts
|

Love matters: exploring conceptions of love in Rwanda and Swaziland and relationship to HIV and intimate partner violence

Abstract: Health risks such as intimate partner violence (IPV) and HIV infection often occur within intimate sexual relationships, yet the study of love and intimacy is largely absent from health research of African populations. This study explores how women and men in Rwanda and Swaziland understand and represent love in their intimate sexual partnerships. In Rwanda, 58 in-depth interviews with 15 couples, 12 interviews with activists, and 24 focus group discussions were carried out during formative and evaluative rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Reduced IPV was identified as a key component of relationship quality, which supports other data suggesting that poor communication is a contributing factor to couple violence (Conroy et al, 2016). Other evidence, including an earlier analysis of the Indashyikirwa program, has suggested that relationship qualities of love, respect, and trust, can be critical antidotes to IPV (Ruark, Stern, Dlamini-Simelane, & Fidele Kakuze, 2017; Starmann et al, 2017). Through a case study comparison, this study illustrates strikingly similar pathways of change to enhance quality of relationships and the broader benefits of couples programming.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced IPV was identified as a key component of relationship quality, which supports other data suggesting that poor communication is a contributing factor to couple violence (Conroy et al, 2016). Other evidence, including an earlier analysis of the Indashyikirwa program, has suggested that relationship qualities of love, respect, and trust, can be critical antidotes to IPV (Ruark, Stern, Dlamini-Simelane, & Fidele Kakuze, 2017; Starmann et al, 2017). Through a case study comparison, this study illustrates strikingly similar pathways of change to enhance quality of relationships and the broader benefits of couples programming.…”
Section: Discussionmentioning
confidence: 99%
“…Our qualitative explorations of the three models suggest that women view gift giving as an important mark of love, affection, and serious intention within romantic relationships; other research in the region has demonstrated similar findings ( Fielding-Miller, Dunkle, Jama-Shai, et al, 2016 ; Ruark et al, 2014 ; Stoebenau et al, 2016 ). Qualitative work from Swaziland and Rwanda conducted by Ruark et al (2017) and published in this special issue suggest that women see gift giving as a tangible way through which they can “see” their partner’s love. The decreased levels of emotional IPV in relationships with higher levels of gift giving suggest that this emic perspective on love is valid and should be heeded by researchers and policy makers from the global North.…”
Section: Discussionmentioning
confidence: 99%
“…Amato (2007) writes that despite love being the primary reason that men and women enter relationships and marry, there is a lack of serious research about the subject. With some notable exceptions (Cole & Thomas, 2009; Hunter, 2010; Lesch & Adams, 2016; Mojola, 2014; Parikh, 2016; Smith, 2001; SĂžlbeck, 2010), this deficit of research is even greater with respect to Africa (Ruark et al, 2017). Whereas historians have argued that romantic love has long been part of African cultures, romantic love as a basis for marriage or other long-term relationships is a more modern phenomenon (Vaughan, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…To date, most research of couples in Africa has focused on violence and power, with less attention to more positive aspects of couple relationships such as love and intimacy (Ruark, Stern, Dlamini-Simelane, & Kakuze, 2017). Gender-based violence and other forms of gendered power inequity are well recognised as having serious detrimental effects on multiple aspects of women’s health (Blanc, 2001; Hatcher et al., 2012; Siedner et al., 2012), including risk of HIV (Dunkle et al., 2004; Jewkes, Dunkle, Nduna, & Shai, 2010).…”
Section: Introductionmentioning
confidence: 99%